Strengthening Salesperson Performance through Psychological Contracts: The Mediating Role of Innovative Work Behavior in Indonesia’s Automotive Service Sector - Hafni, Layla; Safari, Surya; Chandra, Teddy; Suwitho, Suwitho; Suhermin, Suhermin (International Journal of Social Science and Business, 2025)
There are inconsistent findings regarding the influence of psychological contracts on innovative work behavior, with some studies showing no significant relationship while others indicate a strong positive effect, revealing a theoretical gap that needs further exploration. This study addresses that gap by examining how fulfilled psychological contracts, through the lens of Social Exchange Theory, stimulate innovative work behavior and enhance salesperson performance in Indonesia’s competitive automotive service sector. This study examines how psychological contracts influence salesperson performance, both directly and indirectly, through the mediating role of Innovative Work Behavior (IWB). Data were collected through a census of 184 salespeople from an automotive service company in Riau, Indonesia, using a structured questionnaire. Analysis was conducted with SmartPLS 4.1. The results show that psychological contracts significantly affect salesperson performance (β = 0.460, p < 0.01) and IWB (β = 0.904, p < 0.001). In turn, IWB significantly improves performance (β = 0.487, p < 0.001) and mediates the relationship between psychological contracts and performance (β = 0.440, p < 0.001). Theoretically, this study extends Social Exchange Theory by clarifying inconsistent findings on psychological contracts and innovative behavior in prior research. Practically, the results highlight the importance of fulfilling psychological contracts to stimulate innovation and strengthen sales performance in emerging market contexts.